Penataan Terminal Tipe B Kabupaten Sukabumi - Wiyoga Triharto; Bambang Perkasa Alam (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2020)
Ratu harbor beach is one of the mainstay tourist sites for the Regional Government of Sukabumi Regency in bringing PAD, besides public transportation facilities and terminals have a major role in supporting the queen port as a tourist attraction so that tourists are comfortable and facilitated in accessing through public transportation. The condition of the Pelabuhan Ratu Terminal, Sukabumi Regency is currently very poor, poorly maintained, and many supporting facilities are damaged and inadequate. This study aims to identify problems and formulate the type B terminal arrangement in Sukabumi Regency. The method used is descriptive qualitative in order to get a picture of the problems of the situation and conditions currently taking place or occurring in the present and the study of policies. Collecting data by field surveys, literature studies and interviews. The results in this study get a terminal B type terminal design concept Sukabumi Regency according to current and future needs.